Women Against Women: The Limits of Public Visibility in the Early Republican Period - Pınar Aydoğan (Siyasal: Journal of Political Sciences)
It is evident that the modernization process in the early period of the Republic can best be observed through women who undoubtedly had been the main actors of the modern lifestyle that the Republic aimed to create. The changes made in many areas such as law, education, and clothing intended to increase women’s “public visibility”. In the Ottoman period, the existence of women was confined to the private sphere; yet, with the foundation of the Republic, women were now everywhere in society, taking on professional roles as “lawyers, doctors, teachers, pilots, bankers and members of the parliament”. This study will examine an article series titled “Women in Business Life” published in Vakit newspaper in 1929 involving women who were a part of the professional life of the respective period, most of whom were publicly known. The aim of this study is to make an analysis of the women’s movement in the Early Republican period within the framework of the concepts used by the women whose views were shared in the series, their personal experiences, and the relationship they established with women’s rights and nationalism. This study will focus on the points where the basic demands of first-wave feminism and the Republic’s approach to women’s issues/rights in the process of modernization and nation-statehood meet and/or diverge. The document analysis method was used in this study. The Vakit newspaper was scanned and analyzed for the period between March 1929 and May 1929 when the article series was published.